Family Psychoeducation Increases the Role of Families in Caring for People with Mental Disorders - Desak Made Ari Dwi Jayanti; Ni Kadek Yuni Lestari (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Family psychoeducation is a family therapy that combines clinical interventions to increase family understanding in order to improve the health of people with mental disorders. The purpose of this study was to determine the effect of family psychoeducation on the role of the family caring for people with mental disorders. This study used a Quasi Experiment design: pre-test and post-test Control Group Design. The sample was taken by using purposive sampling. The sample was 20 people in the control group and 20 people in the treatment group. The analysis test used was the Wilcoxon sign test (intra-group) and the Mann Whitney (inter-group) test. The  intra-group analysis test in the pre and post-test for the control group obtained p value = 0.517 which means there is no difference, while the treatment group obtained p value = 0.004 which means there is a difference. Inter-group analysis test of the treatment group and the control group obtained p value = 0.008, which means that there is an effect of family psychoeducation on the role of families in caring for people with mental disorders. Family psychoeducation can be applied to families with mentally disorders people.